2018
DOI: 10.1177/1475725718779727
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Clarity About Study Programme Contents and Interest in Student Evaluations of Teaching

Abstract: Validity is an important issue when measuring teaching quality using student evaluations. This study examined the effects of psychology students' subjective clarity about study contents and their prior interest in the subject as variables possibly biasing the evaluations of psychology courses. German students (N ¼ 292) evaluated lectures and seminars over five years with a standardized questionnaire, yielding 3,348 data points. In cross-classified multilevel models, we separated the total variance into the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Bias against instructors with minority racial, ethnic, and foreign cultural backgrounds was another substantive finding in our review (Chávez, 2020;Gith, 2020;Schueths et al, 2013;Socha, 2013;Wang & Gonzalez, 2020), particularly in institutions with less diversity among faculty and students (Fan et al, 2019). SRIs were also positively related to factors such as students' prior interest in course content (Blecich & Zaninović, 2019;Feistauer & Richter, 2018a, 2018bFischer & Hänze, 2019;Sulis et al, 2019;Tarun & Krueger, 2016) and grade expectations (Borkan, 2017;Goos & Salomons, 2017;Radchenko, 2020), and negatively associated with class size (Blecich & Zaninović, 2019;Goos & Salomons, 2017;Jobu Babin et al, 2020;Macfadyen et al, 2016;Risquez et al, 2015;Winer et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Bias against instructors with minority racial, ethnic, and foreign cultural backgrounds was another substantive finding in our review (Chávez, 2020;Gith, 2020;Schueths et al, 2013;Socha, 2013;Wang & Gonzalez, 2020), particularly in institutions with less diversity among faculty and students (Fan et al, 2019). SRIs were also positively related to factors such as students' prior interest in course content (Blecich & Zaninović, 2019;Feistauer & Richter, 2018a, 2018bFischer & Hänze, 2019;Sulis et al, 2019;Tarun & Krueger, 2016) and grade expectations (Borkan, 2017;Goos & Salomons, 2017;Radchenko, 2020), and negatively associated with class size (Blecich & Zaninović, 2019;Goos & Salomons, 2017;Jobu Babin et al, 2020;Macfadyen et al, 2016;Risquez et al, 2015;Winer et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
“…Seven (11.1%) studies examined the influence of students' prior interest in course content on their SRI scores. Prior interest was positively related with SRI scores (Blecich & Zaninović, 2019;Feistauer & Richter, 2018a, 2018bFischer & Hänze, 2019;Sulis et al, 2019;Tarun & Krueger, 2016) and students with a greater prior understanding of the course content provided higher ratings (Sulis et al, 2019). Conversely, Socha (2013) found that prior interest level was negatively associated with SRI ratings, possibly mediated by overly high course expectations.…”
Section: Types Of Biasmentioning
confidence: 99%
“…In other words, the perception of students regarding the conduct of their teachers in class influences their motivation (Frymier & Shulman, 1995). Similarly, the level of motivation towards learning affects the way in which students evaluate their environment (Smimou & Dahl, 2012) and, therefore, the way in which they perceive the teaching given (Feldman, 1998), as, when they show interest in the subject, their evaluation of teacher performance is positive (Feistauer & Richter, 2018a, 2018b.…”
Section: Introductionmentioning
confidence: 99%